Phenological mismatch caused by water regime change may explain the population variation of the vulnerable lesser white-fronted goose in east Dongting Lake, China. (August 2021) - Zhang, Pingyang; Zou, Yeai; Xie, Yonghong; Zhang, Siqi; Zhu, Feng; Chen, Xinsheng; Li, Feng; Deng, Zhengmiao; Yao, Yi; Song, Yucheng
Graphical abstract: Highlights: Water recession pattern were classified as optimal, early, or late water recession. Phenological mismatch is the days between geese arrival and timing of optimal NDVI. Unusually early or late water level recession leads to a greater mismatch. Greater mismatch negatively affected Lesser White-fronted Goose abundance. Greater mismatch resulted in a clumped Lesser White-fronted Goose distribution. Abstract: Phenological mismatches between migratory birds and food availability driven by global warming have been found to influence the fitness and population dynamics of several herbivorous goose species in Arctic breeding sites. However, the effect of phenological mismatches at wintering sites have been inadequately studied. We used long-term data to explore the consequences of water regime changes on phenological mismatch (i.e., days between arrival of geese and timing of the optimal Normalized Difference Vegetation Index [NDVIopt ]) and detect the relative role of the mismatch as a driver of annual variations in abundance and distribution of the Lesser White-fronted Goose Anser erythropus (a vulnerable species on the IUCN Red List) in East Dongting Lake, which is the one of this species' largest wintering sites worldwide. The NDVI of the Carex meadow (i.e., the dominant vegetation in East Dongting Lake wetland and also the major food resource for the geese) was used as the phenology metric. Results showed that the water recession pattern greatly influenced food conditions when geese arrived at the site. Early water recession led to significantly higher NDVI, whereas late water recession led to significantly lower NDVI than did the optimal water recession. However, the suitable habitat area was significantly larger under the optimal water recession pattern. Both early and late water level recessions caused greater mismatches and resulted in lower geese abundance and a more concentrated distribution. NDVI was positively correlated with aboveground biomass and negatively correlated with N% of Carex spp. High biomass and low N% related to high NDVI caused by early water recession may indicate unfavorable food conditions at the time that geese arrive and reduced sustainable food availability in mid-winter, while a low NDVI and limited habitat area caused by late water recession may indicate an insufficient food supply. In conclusion, non-optimal water recession led to a greater phenological mismatch and resulted in limited habitat quality (e.g., lower leaf N%) under early water recession but limited habitat quantity (e.g., smaller habitat area and lower aboveground biomass) under late water recession, and ultimately threatened the Lesser White-fronted Goose. Our results contributed to explaining the decline of the Lesser White-fronted Goose population in this wintering site.